2001
DOI: 10.1143/jjap.40.656
|View full text |Cite
|
Sign up to set email alerts
|

Influence of One Monolayer Thickness Variation in GaAs/AlGaAs Five-Layer Asymmetric Coupled Quantum Well upon Electrorefractive Index Change

Abstract: The five-layer asymmetric coupled quantum well (FACQW) is a new potential-tailored quantum well (QW) for ultrafast and low-voltage optical modulators and switches. First, the influence of one monolayer (ML) thickness variation of a single layer in the GaAs/AlGaAs FACQW on the electrorefractive index change Δn is theoretically studied. The thickness variation of two thicker GaAs layers has a considerable influence on Δn of the FACQW, while the thickness variation of thin AlAs and AlGaAs barrier layers has a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…This value is about half of the theoretically expected one. This discrepancy is probably due to thickness fluctuations of each layer [3].…”
Section: Gaas/algaas Facqw Mach-zehnder Modulatormentioning
confidence: 99%
“…This value is about half of the theoretically expected one. This discrepancy is probably due to thickness fluctuations of each layer [3].…”
Section: Gaas/algaas Facqw Mach-zehnder Modulatormentioning
confidence: 99%
“…The Lorentzian broadening function used in the model is described in [9], and the refractive-index changes are obtained using the Kramers-Kronig relation [1]. Our model is very similar to that used in [3] and [10] except that, in our model, the refractive-index changes are obtained for a whole period of a CQW structure and not only for the quantum-well layers. Fig.…”
Section: Influence Of Layer Variationsmentioning
confidence: 99%
“…In [3], it is shown that even such small thickness variations can significantly modify the distributions of wave functions in CQW structures and, in turn, influence the absorption spectra and the refractive-index changes in these structures. Similarly, the InAs mole fractions in the three barriers and each quantum well are changed by ±0.02.…”
Section: Influence Of Layer Variationsmentioning
confidence: 99%
See 2 more Smart Citations